Metodologías para establecer valores de referencia de metales pesados en suelos agrícolas: perspectivas para colombia (2011)
From an environmental perspective, the importance of heavy metals in soils is related to their toxicity either due to their accumulation or to any interaction between them and some of their specific properties.  In each case, heavy metals can move through the soil profile and transfer into the trophic chain through water bodies or crops affecting human health.  In developed countries, the establishment of baseline values has permitted improvements in the soil environmental management plans.  Baseline values have become a control tool for environmental agencies to test the impact of heavy metals in a variety of agricultural activities.  This article analyses different concepts related to heavy metals levels in agricultural soils and the effects of soil characteristics on their concentration, at the same time some methodologies to obtain specific baseline values from identification of the natural concentration are reviewed.  It is included some prospects related to soil protection and remediation in Colombia.  Currently, in Colombia there are no studies related to obtain baseline values of heavy metals in agricultural soils.  For this reason it is necessary to get support from agencies such as the Ministry of Environment, Housing and Territorial Development and Ministry of Agriculture, in order to start and develop research in some primary agricultural sectors to guarantee the production and the environmental sustainability of soils.